Determinan Tingkat Pengetahuan IMS pada Remaja Perempuan di Indonesia Tahun 2017 - Annisa Salsabila Aulia; Efri Diah Utami (Politeknik Statistika STIS, 2022)
Sexually Transmitted Infections (STIs) is a health problem that often occurs in the global. Beside health problems, STIs are also one of the causes of social and economic problems in many countries. The exact cases number of STIs are not yet known in Indonesia. This makes the spread of STIs are difficult to trace its source. Therefore, in order to reduce the cases of STIs, it can approached by increasing public knowledge about STIs . This study aims to determine the general description and the effect of education level, welfare level, age, area of residence, and mass media access on the level of knowledge about STIs among Indonesian adolescent girls in 2017. In achieving this goal, data from Demographic and Health Survey (DHS) 2017 were analyzed using binary logistic regression method. The results of this study indicate that adolescent girls who have a good level of knowledge mostly graduating from high school, a rich level of welfare, 20-24 years old, living in urban areas, accessing newspapers, radio, television, and the internet. The level of STI knowledge among Indonesian adolescent girls is influenced by education level, welfare level, age, area of residence, access to newspapers, radio access, and internet access.